Strategi Sektor Kesehatan Dalam Meningkatkan Indeks Pembangunan Manusia Di Kabupaten Situbondo - Arif Tristanto; Herman Cahyo Diartho (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2018)
The success of a development is not only seen from the level of economic growth but also from the level of community welfare as well as a benchmark for the success of the development of a region. The Human Development Index covers three indices, namely the education index, health index, and purchasing power index. In this study one of the indicators in improving the human development index is the health index. Judging from the growth rate of the Situbondo District human development index (HDI), the health index growth during 2012-2016 remained at 0.74 and the growth of the human development index (HDI) in Situbondo was still below the growth of the human development index (HDI) in East Java Province. The formulation of the problem taken in this study is how to synthesize strategies in improving the Human Development Index (HDI) in the health sector in Situbondo District. The analytical method used uses analytical hierarchy process. The results of the analysis analysis obtained the strategy used in improving the human development index in Situbondo District in the health sector, namely health services became a priority in improving the human development index in the health sector in Situbondo District by 0.136, and both health budgets by 0.059, and the three health sector institutions by 0.018.